Penyuluhan Anti-Bullying Berbasis Humanistik Di SMP Negeri 2 Siantar: Kegiatan Pengabdian kepada Masyarakat - Vera Wati Malau; Devira Ekklesia Sinaga; Erikson Aprianto Tarihoran; Cinta Yulistra Tindaon; Putri Anastasia Silalahi; Bella Artika Aritonang; Yessika Meliana Simarmata; Rudiarman Purba (Young Journal of Social Sciences and Humanities, 2026)
Bullying in schools remains a problem that affects students’ comfort, mental health, and social development. This condition highlights the need for preventive efforts that do not focus solely on the enforcement of rules, but also aim to enhance students’ awareness and empathy. This article aims to describe the implementation of a Community Service activity in the form of humanistic-based anti-bullying counseling conducted at SMP Negeri 2 Siantar. The activity was carried out through several stages, including problem identification, planning, counseling implementation, reflection, and evaluation. The counseling involved students and teachers and was delivered using interactive methods through discussions and shared reflection. The results of the activity indicate that students gained a deeper understanding of the types and impacts of bullying and began to demonstrate more caring and respectful attitudes in their daily interactions. This activity contributes positively to bullying prevention efforts and supports the creation of a safe, comfortable, and humane school environment.